2018
DOI: 10.1001/jamadermatol.2018.2972
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Therapies for Psoriasis

Abstract: IMPORTANCE Up to 51% of patients with psoriasis report the use of complementary and alternative medicine (CAM) in their treatment regimen, although it is unclear which CAM therapies are effective for treatment of psoriasis.OBJECTIVE This review compiles the evidence on the efficacy of the most studied CAM modalities for treatment of patients with plaque psoriasis and discusses those therapies with the most robust available evidence. PubMed, Embase, and ClinicalTrials.gov searches (1950-2017) were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 53 publications
1
57
1
7
Order By: Relevance
“…Psoriasis is a chronic, immune-mediated skin disease that shows red and scaly patches on the skin that itch or burn. Three systematic reviews have evaluated the use of herbal therapies in psoriasis [23][24][25].…”
Section: Psoriasis Vulgarismentioning
confidence: 99%
“…Psoriasis is a chronic, immune-mediated skin disease that shows red and scaly patches on the skin that itch or burn. Three systematic reviews have evaluated the use of herbal therapies in psoriasis [23][24][25].…”
Section: Psoriasis Vulgarismentioning
confidence: 99%
“…Pflanzliche Wirkstoffe spielen auch bei der Behandlung der Psoriasis eine Rolle. Vor kurzem erschienen 2 ausführliche, systematische Reviews, die die Studien zu diesem Thema analysieren und bewerten [26,27].…”
Section: Psoriasis Vulgarisunclassified
“…In current, there is lack of comparative effectiveness studies using acupuncture related techniques for plaque psoriasis. Systematic reviews have reported the benefit of needling, but with relatively low methodological quality [26] and lacking of comparison of effect to different interventions [27].…”
Section: Rational For the Trial Designmentioning
confidence: 99%